PERUBAHAN ARTIKULASI FONEM BAHASA ARAB BAGI PENUTUR BAHASA ASING - Rossi Delta Fitrianah (IAIN Bengkulu, 2019)
The impact of the articulation of the second language phonemes will lead to mistaken meanings. Pronounced mistakes made by second language speakers will confuse the speaker, especially the native speaker. Mistakes of meaning and misinterpretation result in communication not working properly. Research Objectives 1.) to indicate Arabic phonemes that often occur in articulation changes for Arabic IAIN Bengkulu students. 2.) to find out the factors that influence changes in the articulation of Arabic phonemes for students of IAIN Bengkulu Arabic Language Study Program. The research approach used in this study is a qualitative approach with the type of phenomenological research this study aims to reveal the phenomenon of changes in the articulation of Arabic phonemes for students of the Arabic IAIN Bengkulu Study Program and the factors that influence it. This research is a qualitative descriptive study. Based on the data, it is known that the error rate of Arabic phoneme articulation in the fourth semester students of PBA Study Program is known that there are several forms of Arabic phoneme pronunciation errors that are often found, namely: هـ, ف, ذ, ث The factors that cause the articulation errors of Arabic phoneme IV semester students of Study Program PBA Because of the intersection between Arabic and Indonesian (Interference), which is a mistake caused by the carrying out of the habits of spoken language or dialect of the mother into the second language or dialect. Lack of Motivation to master Arabic articulation in accordance with the rules. Lack of mastery in the pronunciation of the Arabic phoneme There are several factors for speech disordersKeywords: articulation, phonemes, foreign speakers